N-type TOPCON battery and manufacturing method of high-sheet-resistance low-wet-weight back grid line of N-type TOPCON battery

By using specific formula silver paste, including silver powder, glass frit and organic carrier, the problem of the contact capability of the back fine grid under high square resistance and low humidity weight is solved, and excellent sintering windows and printing capabilities are achieved, and the conversion efficiency of the battery is improved.

CN119677223APending Publication Date: 2025-03-21JUHE (YIBIN) NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411917081.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing N-type TOPCON batteries are difficult to balance the opening pressure and efficiency performance under the conditions of improving the high square resistance and low humidity weight of the back fine grid, resulting in a decrease in the contact capacity of the metal contact area on the back, affecting the conversion efficiency of the battery cells.

Method used

The silver paste with a specific formula is used to prepare the back side silver grid wire. The silver paste includes silver powder, glass frit and organic carrier. The glass frit consists of tellurium-lead-lithium oxide and a variety of metal oxides. The glass transfer temperature is less than 800°C and the softening temperature is less than 550°C to achieve excellent sintering window and printing capabilities.

Benefits of technology

Under high square resistance and low humidity conditions, a wide sintering window and good efficiency performance are achieved, and a good narrow line width printing system is also provided, which improves the conversion efficiency of the battery cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an N-type TOPCON battery and a manufacturing method of a high-sheet-resistance low-wet-weight back grid line of the N-type TOPCON battery. The preparation method comprises the steps of adopting selected silver paste to form a grid line precursor and sintering the grid line precursor to form a grid line. Wherein the selected silver paste comprises silver powder, a glass material and an organic carrier; the glass frit includes a primary glass system including a tellurium-lead-lithium oxide and a secondary glass system including oxides of a plurality of selected metals. The preparation method provided by the invention is matched with a corresponding high sheet resistance process of a solar cell manufacturer, a wider sintering window and good efficiency performance can be obtained under the condition of reducing the wet weight, and meanwhile, a good narrow linewidth printability system, an excellent sintering window and good printing capability are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cells, and in particular to an N-type TOPCON cell and a method for manufacturing a back grid line thereof with high square resistance and low wet weight. Background Art

[0002] In the past, the development trend of N-type TOPCON battery technology was that most battery manufacturers used alkaline polishing for the back side polishing, and the main process routes were LP, LP dual insertion, PECVD, etc. For the LP process route, the back side resistance promoted by battery manufacturers is now in the range of 40-55Ω / sq. The LP process is used to tunnel the oxide layer and polysilicon layer of the N-type back silicon substrate. Under the conditions of fixed polysilicon layer design thickness and doping concentration, phosphorus doping will penetrate the silicon dioxide layer and when penetrating the diffusion profile, the passivation of the fine gate on the back side of the battery reaches the most ideal value. The improvement of the back side resistance in the later stage requires the improvement of contact and corrosion capabilities, while reducing efficiency loss, thereby building an inorganic system that matches the high back side resistance.

[0003] As the screen printing stencil conditions for the back side fine grid become more and more demanding, from high film thickness and high yarn thickness matching 20-micron line width conditions, the current low film thickness and low yarn thickness matching line width is narrowed to 10 microns. The back side fine grid printing conditions have reached the printing and efficiency bottleneck. The main purpose of adjusting the back side fine grid stencil is to match the requirements of battery manufacturers to reduce wet weight. However, reducing wet weight will also bring about the loss of inorganic contact, and can affect the FF value and high interface passivation effect, and finally affect the contact of the back side metal contact area, and even affect the efficiency performance.

[0004] It can be seen that as solar cell manufacturers require the back side fine grid to reduce wet weight, while matching the high square resistance-LP process high opening voltage route, balancing the opening voltage and FF performance, and compensating for the contact of the back side paste under reduced wet weight conditions, the efficiency of the cell is ultimately improved. For the back side fine grid silver paste under high square resistance and low wet weight conditions, higher requirements are placed on the corrosion degree and contact ability of the silicon substrate. This factor restricts the conversion efficiency of the cell. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide an N-type TOPCON battery and a method for manufacturing a back grid line with high square resistance and low wet weight.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: In a first aspect, the present invention provides a method for preparing a back silver grid line with high square resistance and low wet weight of an N-type TOPCON battery, which comprises the steps of forming a grid line precursor by using a selected silver paste and sintering the grid line precursor to form a grid line; Wherein, the selected silver paste comprises silver powder, glass frit and organic carrier; The glass frit comprises a main glass system and a secondary glass system, wherein the main glass system comprises tellurium-lead-lithium oxide, the secondary glass system comprises oxides of multiple selected metals, and has a glass transition temperature lower than 800° C. and a softening temperature lower than 550° C.

[0007] In a second aspect, the present invention further provides an N-type TOPCON battery, wherein the back side grid line of the N-type TOPCON battery is prepared by the above-mentioned back side silver grid line preparation method; The square resistance of the back gate line is 40-55Ω / sq.

[0008] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include: The preparation method provided by the present invention matches the corresponding high square resistance process of solar cell manufacturers, and can obtain a wider sintering window and good efficiency performance under reduced wet weight conditions. At the same time, it has a good narrow line width printability system, and has an excellent sintering window and good printing ability.

[0009] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention. DETAILED DESCRIPTION

[0010] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.

[0011] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0012] An embodiment of the present invention provides a method for preparing a back silver grid line with high square resistivity and low wet weight of an N-type TOPCON battery, which includes the steps of using a selected silver paste to form a grid line precursor and sintering the grid line precursor to form a grid line; wherein the selected silver paste includes silver powder, glass material and an organic carrier; the glass material includes a main glass system and a secondary glass system, the main glass system includes tellurium-lead-lithium oxide, the secondary glass system includes oxides of multiple selected metals, and the glass transition temperature is lower than 800°C and the softening temperature is lower than 550°C.

[0013] Among them, the high square resistance process has a lower surface impurity concentration, which effectively reduces the impurity recombination center on the surface, improves the survival rate of surface minority carriers, and increases the short-wave response, thereby effectively increasing ISC and Uoc to achieve the purpose of improving efficiency.

[0014] In the above technical scheme, the present invention first adds the Te-Pb-Li main glass system. During sintering, some of the three oxide elements have a high corrosive effect on silicon nitride, and some of the oxides can diffuse into the silicon layer to increase the open circuit voltage. The other secondary glass systems and the silver powder system control the fluidity during the melting process, and the sintering channels of silver and silicon are denser, which can ensure the back sintering window; the secondary glass system X has a lower glass transition temperature and softening temperature, and the X oxide contains a network exosome product, which has good fluidity for the substrate to obtain a wide contact area, and the glass system contained in X is corrosive, thereby obtaining a lower contact resistance.

[0015] From the above principles, it can be seen that the main design idea of ​​the technical solution provided by the present invention lies in the coordination of the Te-Pb-Li main glass system and the corresponding sub-glass system. Although some existing technologies provide a glass system for designing Te-Pb-Li oxide and its application in metal conductive paths and emitter electrodes (such as the Chinese invention patent with publication number CN104271527A), it is not used for the preparation of high-resistance and low-wet-weight back silver grid lines of N-type TOPCON batteries, but only reflects the application in emitter electrodes, and cannot guide technical personnel in this field to solve the problems faced by the high-resistance and low-wet-weight back process of N-type TOPCON batteries.

[0016] Regarding the specific ratio of each component, in some embodiments, the mass fraction of the silver powder is 80-90%, the mass fraction of the main glass system is 1-4%, the mass fraction of the secondary glass system is 0.1-2%, and the balance is the organic carrier. The mass fraction of the organic carrier in a typical implementation case is 7-12%.

[0017] In some embodiments, the mass ratio of tellurium-lead-lithium elements in the main glass system is (10-40):(10-40):(1-10).

[0018] As for some specific characteristics of each main component, in some embodiments, the silver powder adopts high tap density dispersed spherical silver powder with a particle size of 1.0-2.5 μm and a specific surface area of ​​0.2-1.0 m 2 / g, and the tap density is 3-8g / ml.

[0019] In some embodiments, the secondary glass system includes any one or a combination of two or more of magnesium oxide, sodium oxide, tungsten oxide, zinc oxide, cesium oxide, strontium oxide, tin oxide, and aluminum oxide.

[0020] In order to match the extremely demanding screen conditions of battery manufacturers and match low film thickness and low yarn thickness narrow line width screens, the present invention can adopt an organic carrier with good dispersibility, stable uniformity and strong bonding performance. The organic carrier can maintain a certain fluidity and good printability as well as a good line shape. Through metallization to the store slurry screen printing and sintering process, it is chemically stable and has a low residual ash content after burning. It can be widely used in back-side fine grid slurry. The organic carrier maintains better shaping and can solve the problem of silver powder de-gridding encountered after the resin and solvent are dried during the DUP printing process.

[0021] In some specific embodiments, the organic vehicle includes a binder, a solvent, a thixotropic agent, a dispersant, and a surfactant.

[0022] In some embodiments, the mass ratio of the binder, solvent, thixotropic agent, dispersant and surfactant is (1-10): (5-10): (0-5): (0-3): (0-5).

[0023] In some embodiments, the organic synthetic resin is used as a binder, and acts as a binder between the powder and the glass powder in the silver paste. The main components are resin and solvent, which are mixed in a corresponding proportion and then heated and dispersed. The binder includes any one or a combination of two or more of ethyl cellulose, PVB Mowital, diethylene glycol butyl ether acetate, dimethyl adipate, modified acrylic resin, phenolic resin, CAB, rosin resin, epoxy resin, and DBE. In general, the solvent carrier content in the binder itself is about 40-90wt%, and the solvent mentioned above is additionally added when preparing the silver paste.

[0024] In some embodiments, the dispersant includes any one or a combination of two or more of 12-hydroxystearic acid, oleamide, erucamide, sodium tripolyphosphate, sodium pyrophosphate, alkylbenzene sulfonate, dialkyl sulfosuccinate, polyoxyethylene alkylphenol ether, and vinyl bisstearamide.

[0025] In some embodiments, the surfactant includes any one or a combination of two or more of polyethylene glycol, sodium linear alkylbenzene sulfonate, sodium lauryl sulfate, lauroyl glutamic acid, nonylphenol polyoxyethylene ether, lignin sulfonate, alkyl sulfonate, fatty alcohol polyoxyethylene ether, and fatty alcohol polyoxyethylene ether sodium sulfate.

[0026] In some embodiments, the thixotropic agent includes any one or a combination of two or more of polyamide wax, modified hydrogenated castor oil, fumed silica, polyethylene wax, and alkyl alcohol ether.

[0027] In some embodiments, the wet weight of the gridline precursor is 30-35 mg.

[0028] The silver paste used in the above preparation method can be prepared based on the above group ratio, dispersed by stirring, double-rolled to a fineness of less than 6 microns, and ground and sieved to obtain the silver paste.

[0029] The second aspect of the embodiment of the present invention further provides an N-type TOPCON battery, wherein the back side grid line of the N-type TOPCON battery is prepared by the back side silver grid line preparation method provided by any of the above embodiments; the square resistance of the back side grid line is 40-55Ω / sq.

[0030] The technical solution of the present invention is further described in detail below through several embodiments. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.

[0031] In the following embodiments, the silver powder used is: N-type TOPCON battery high square resistance low wet weight lower back fine silver paste preparation, the main glass material and the auxiliary glass material are mixed, high temperature melting, cooling and using the planetary ball milling method to screen to obtain a powdered glass material with a suitable particle size, the D50 particle size of the glass powder obtained from the above preparation process is in the range of 1.0-3.4μm, and the spherical silver powder with a high tap density is selected. 80-89%, the tap density range is 5-9g / ml, the silver powder particle size D50 range is 1-2.0μm, and the specific surface area is 0.3-0.6m 2 / g.

[0032] Glass powder: Glass powder is mainly Pb-Te-Li system, compounded with X oxide, and the overall glass content is in the range of 1.5-3.0%.

[0033] Organic carrier: The overall organic part contains 8-10% range, specifically including binder, solvent (extra), thixotropic agent, dispersant, surfactant.

[0034] Comparative Example 1 Baseline: As shown in Table 1 and Table 2, 88.6wt% conductive silver powder, 0# glass powder: 2.8wt%, resin 3%, additive 3.5wt%, thixotropic agent 1.3%wt%, dispersant: 0.8wt%, double-roll rolling method is used for grinding, and the slurry fineness is maintained below 6 microns. The obtained slurry is named Comparative Example 1.

[0035] Example 1 88.6wt% conductive silver powder, 2.8wt% glass powder 1, 3wt% resin, 3.5wt% additive, 1.3%wt% thixotropic agent, and 0.8wt% dispersant were used. The slurry was ground by double-roll rolling, and the slurry fineness was kept below 6 microns. The slurry was named S1.

[0036] Example 2 This embodiment is substantially the same as embodiment 1, and the main difference is the different proportions of components, as shown in Table 1 and Table 2, and the obtained slurry is named S2.

[0037] Example 3 This embodiment is substantially the same as embodiment 1, and the main difference is the different proportions of components, as shown in Table 1 and Table 2, and the obtained slurry is named S3.

[0038] Example 4 This embodiment is substantially the same as embodiment 1, and the main difference is the different proportions of components, as shown in Table 1 and Table 2, and the obtained slurry is named S4.

[0039] The glass powder ratio and slurry component ratio provided in the above comparative examples and embodiments are shown in the following two tables: Table 1 Glass powder ratios in the examples and comparative examples

[0040] Table 2 Slurry component ratios in the examples and comparative examples

[0041] Test Case First, the corresponding formula ingredients are mixed and dispersed, three-roller rolling is performed to obtain the back fine grid silver paste, which is then printed on the silicon wafer by a printer according to the corresponding parameters. The printed silicon wafer is collected in the drying area, and after printing, it is ready for testing after a series of processes such as sintering furnace, light injection, and LECO laser. The main tests are the efficiency of the battery, the 3D line type on the back, and EL. The 3D line type can indicate the height, width, and aspect ratio of the grid line to determine the flatness and undulation of the line type.

[0042] According to the corresponding N-type TOPCON back fine silver paste S1-S4 obtained in Examples 1-4 and the control example back fine silver paste, the efficiency and EL test results of N-type TOPCON back fine silver paste prepared by printing and sintering are shown in the following table:

[0043] The results in the above table show that matching the high square resistance process and the contact of S2, S3 and S4 samples under extremely low wet weight conditions have improved, and the series resistance has also obtained a corresponding gain. In this case, EL is observed to hold a wider sintering window.

[0044] The above results show that the N-type TOPCON cell back fine silver paste made in this case can achieve the design purpose of the present invention. The present invention mainly matches the high square resistance process of solar cell manufacturers, and can obtain a wider sintering window and good efficiency performance under the condition of reducing wet weight, and at the same time has a good narrow line width printing system. Therefore, the glass material provided by the present invention and the corresponding organic carrier are used to prepare the N-type TOPCON back fine silver paste, so that the silver paste has an excellent sintering window and good printing ability.

[0045] Based on the above embodiments and comparative examples, it can be clearly seen that the preparation method provided in the embodiments of the present invention matches the corresponding high square resistance process of solar cell manufacturers, and can obtain a wider sintering window and good efficiency performance under reduced wet weight conditions, while having a good narrow line width printing system, with an excellent sintering window and good printing capability.

[0046] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a back silver grid line with high square resistance and low wet weight for an N-type TOPCON battery, characterized in that: The method comprises the steps of using a selected silver paste to form a gate line precursor and sintering the gate line precursor to form a gate line; Wherein, the selected silver paste comprises silver powder, glass frit and organic carrier; The glass frit comprises a main glass system and a secondary glass system, wherein the main glass system comprises tellurium-lead-lithium oxide, the secondary glass system comprises oxides of multiple selected metals, and has a glass transition temperature lower than 800° C. and a softening temperature lower than 550° C.

2. The method for preparing back silver grid lines according to claim 1, characterized in that: The silver powder has a particle size of 1.0-2.5 μm and a specific surface area of ​​0.2-1.0 m 2 / g, and the tap density is 3-8g / ml.

3. The method for preparing back silver grid lines according to claim 2, characterized in that: The mass ratio of tellurium-lead-lithium elements in the main glass system is (10-40): (10-40): (1-10).

4. The method for preparing back silver grid lines according to claim 1, characterized in that: The mass fraction of the silver powder is 80-90%, the mass fraction of the main glass system is 1-4%, the mass fraction of the secondary glass system is 0.1-2%, and the balance is the organic carrier.

5. The method for preparing back silver grid lines according to claim 1, characterized in that: The secondary glass system includes any one of magnesium oxide, sodium oxide, tungsten oxide, zinc oxide, cesium oxide, strontium oxide, tin oxide, and aluminum oxide, or a combination of two or more thereof.

6. The method for preparing back silver grid lines according to claim 1, characterized in that: The organic vehicle includes a binder, a solvent, a thixotropic agent, a dispersant and a surfactant.

7. The method for preparing back silver grid lines according to claim 6, characterized in that: The mass ratio of the adhesive, solvent, thixotropic agent, dispersant and surfactant is (1-10): (5-10): (0-5): (0-3): (0-5).

8. The method for preparing back silver grid lines according to claim 6, characterized in that: The adhesive includes any one or a combination of two or more of ethyl cellulose, PVB Mowital, diethylene glycol butyl ether acetate, dimethyl adipate, modified acrylic resin, phenolic resin, CAB, rosin resin, epoxy resin, and DBE; And / or, the dispersant includes any one or a combination of two or more of 12-hydroxystearic acid, oleamide, erucamide, sodium tripolyphosphate, sodium pyrophosphate, alkylbenzene sulfonate, dialkyl sulfosuccinate, polyoxyethylene alkylphenol ether, and vinyl bisstearamide; And / or, the surfactant includes any one or a combination of two or more of polyethylene glycol, sodium linear alkylbenzene sulfonate, sodium lauryl sulfate, lauroyl glutamic acid, nonylphenol polyoxyethylene ether, lignin sulfonate, alkyl sulfonate, fatty alcohol polyoxyethylene ether, and fatty alcohol polyoxyethylene ether sodium sulfate; And / or, the thixotropic agent includes any one or a combination of two or more of polyamide wax, modified hydrogenated castor oil, fumed silica, polyethylene wax, and alkyl alcohol ether.

9. The method for preparing back silver grid lines according to claim 1, characterized in that: The wet weight of the grid line precursor is 30-35 mg.

10. An N-type TOPCON battery, characterized in that: The back side grid line of the N-type TOPCON battery is prepared by the back side silver grid line preparation method according to any one of claims 1 to 9; The square resistance of the back gate line is 40-55Ω / sq.

Citation Information

Patent Citations

  • Glass composition and its use in conductive silver paste

    CN104271527A

Cited By

  • Solar cell and preparation method thereof, laminated cell and photovoltaic module

    CN121815807A